Implementation of Administration System In Assisting Pelyanan To The Community at SinarKasih Hospital GKST Tentena City Poso District. State University Administration Sam Ratulangi Manado - Mekutika, Andi Preliis; Posumah, Johnny Hanny; Pombengi, Jericho (Sam Ratulangi University, 2017)
ABSTRACTservice process to the public in order to be able to produce the output of excellent information, fast, efficient, and accurate information provided to the community. Implementation of administrative system has not run well, so this research to answer the question how the implementation of hospital administration system in helping the service to the community. In this research, the researcher limits through some elements which can influence the running of administration system which stated by Azrul (2010): Input (Human Resources and Facilities), Process (Steps), Output (Service produced) and Researcher also see Of behavioral factors or attitudes that hospital employees have in supporting the implementation of administrative systems to help service to the community. This research uses descriptive qualitative approach method through interviewing 10 informants, observation, and tracing of additional document in the form of list of interview guides, recorder and write. The results of this study show that in general the application of administrative systems in helping service to the community has not run well.Keywords: Implementation of Admistrais System in Helping Community Service (Input, Process, Output and Attitude)